Motor performance and nutritional status of schoolchildren with and without developmental coordination disorder. DOI: 10.5007/1980-0037.2011v13n1p59 - Thaís Silva Beltrame; Talita Barbosa Miranda; Talita Barbosa Miranda; Thaís Silva Beltrame; Fernando Luiz Cardoso; Fernando Luiz Cardoso (Universidade Federal de Santa Catarina, 2011)
The objective of this study was to investigate the motor performance and nutritional status of schoolchildren aged 7 to 10 years with developmental coordination disorder (DCD). A total of 380 children from public schools in Florianópolis, SC, Brazil, participated in the study. The Movement Assessment Battery for Children (MABC-2) was used for the identification of motor difficulties. Weight and height were measured and the body mass index (BMI) was calculated for the evaluation of nutritional status. The results showed that 6.1% (n=23) of the students presented signs of DCD, including 18 boys and 5 girls. In the group with DCD, a significant difference was observed between manual dexterity skills and aiming/catching skills and between aiming/catching skills and balance. Regarding nutritional status, 85.5% of all students were eutrophic and 12.9% were obese. In the group with DCD, 91.3% of the students were eutrophic and 8.7% were obese. There was no association between nutritional status and motor performance in the two groups, indicating that nutritional status did not influence motor performance in the schoolchildren studied.